Synthesis and sorption properties of zeolite ZSM-5 - Masdan, Saiful Adli (2000)
Zeolite ZSM-S was synthesised by using SDS or the mixture of TPA/SDS as a templating agent. There is no significant difference in the X-Ray Diffraction (XRD) pattern observed among zeolites synthesised using different templating agents. This indicated that zeolites of similar crystallinity were formed. However. slightly different surface area, porosity and morphology of the zeolites were observed, when different ratio of TPA/SDS were used as a templating agents. Zeolites A, X and ZSM-5 were found to be an effective ion exchanger for lanthanum and yttrium ions from aqueous solutions. High metal ion uptake was achieved at initial pH solution of 4.0-4.5 with different conditions to avoid chemical precipitation. The microwave-assisted method showed that it could accelerate the metal sorption process by about 500 times compared to the conventional method. The zeolites loaded with lanthanum and yttrium ions significantly improved the sorption capacity of zeolite towards arsenic ions. Experimental conditions such as pH, initial concentrations, adsorbent dosage and temperature have been optimised to utilise zeolite as an adsorbent for the removal of arsenate ion from aqueous solution. An data fitted the Langmuir and Freundlich isotherms. The zeolites were found to be an ineffective color removal agent for natural peat water and humic acid.